Lithuanian language teaching program developed by Jonas Jablonskis - Naikelytė , J. (Psichologija, 1971)
J. Jablonskis develops the Lithuanian language teaching program for primary school right after the press ban was cancelled by czar. He focused on didactical requirements and psychological age features with a view to the development of oral and written language and logical thinking of students. The main principal when creating the program is scientific basis. The program also provides with phonetic and morphological features of Lithuanian language so the primary school students receive scientific knowledge about the language. The program includes methodical guidelines, thus the author takes into account the methodical aspect of teaching Lithuanian language.